Синтез емкостных энергоисточников для высоковольтных электротехнологических установок с учетом предразрядных процессов - Вовченко, А. И.; Дивак, Н. П. (НТУ "ХПИ", 2010)
Методом чисельного моделювання з урахуванням передрозрядних процесів проведено дослідження впливу параметрів електродних систем та робочого середовища (води) на вибір параметрів ємнісного енергоджерела (L, C, Uз) високовольтної електротехнологічної установки, яка працює у заданому енергетичному режимі та при мінімумі відносних передпробивних втрат енергії. Виконано аналіз та узагальнення результатів розрахунків.

According to the method of numerical modeling, taking into the account processes preceded a discharge, the investigation of the influence of electrode system parameters and operation surroundings (water) on the choice of capacity power supply parameters (L, C, Uз) of high voltage electrotechnical machine which works in specified energy mode with the minimum of relative energy losses preceded a discharge is made. Analysis and generalization of the calculation results are carried out.
Keywords: электрогидроимпульсные технологии; трансформация энергии; плазменный канал; деформации; энергетические параметры; конденсированные среды; высоковольтный пробой